Functionalization of biochar derived from lignocellulosic biomass using microwave technology for catalytic application in biodiesel production. (1st April 2017) - González, M.E.; Cea, M.; Reyes, D.; Romero-Hermoso, L.; Hidalgo, P.; Meier, S.; Benito, N.; Navia, R.
Graphical abstract: Highlights: Biochar-based catalyst synthesis was feasible using microwave assistance (MW). MW transesterification and esterification of waste cooking oil (WCO) was feasible. The methyl ester yield can reach 75% in 15 min using the functionalized biochar. WCO conversion via MW in successive cycles is feasible when the catalyst is washed. Abstract: A study to produce an efficient catalyst to be used for biodiesel production was carried out introducing sulfonic groups in biochar using a microwave reactor. The transesterification reaction of waste cooking oils using the catalyst was also evaluated in a microwave reactor. The results showed that an increase in the temperature up to 140 °C during biochar sulfonation enhanced the SO3 H content on the catalyst surface. These results were confirmed through FT-IR and XPS analyses. A reduction in the surface area of the biochar was observed during the sulfonation. An increase of SO3 H groups on the biochar surface was responsible for a higher FAME yield close to 90%. The catalyst could be re-used for up to six cycles by washing with hexane.